2014
DOI: 10.1074/jbc.m113.504472
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Activation of Guanylate Cyclase Pushes the α1 Signaling Helix and the β1 Heme-binding Domain Closer to the Substrate-binding Site

Abstract: Background: NO-induced conformational changes of guanylate cyclase were analyzed. Results: FRET experiments show a movement of two tryptophans toward a fluorescent substrate. Conclusion: Activation is transmitted to the catalytic domain by direct interaction of the heme binding domain and through the coiled-coil helix. Significance: The results help to advance understanding of the molecular events associated with activation of NOsGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The PAS—helical junction may serve as a flexible pivot point for releasing the inhibitory inter-domain contacts. In support of this model, a recent study employing Förster resonance energy transfer revealed NO-induced proximity changes between the sGC H-NOX and catalytic domains (Busker et al, 2013). On the other hand, the possibility that the PAS—helical junction exerts long-range effects through helical domain conformational changes cannot be ruled out (Figure 6B).…”
Section: Discussionmentioning
confidence: 75%
“…The PAS—helical junction may serve as a flexible pivot point for releasing the inhibitory inter-domain contacts. In support of this model, a recent study employing Förster resonance energy transfer revealed NO-induced proximity changes between the sGC H-NOX and catalytic domains (Busker et al, 2013). On the other hand, the possibility that the PAS—helical junction exerts long-range effects through helical domain conformational changes cannot be ruled out (Figure 6B).…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, in our maps of both unliganded and NO-bound sGC we observe that the H-NOX domain can make direct contact with the catalytic domain, which could contribute to allosteric control of the catalytic domain by the H-NOX. Busker et al (28) recently proposed a mechanism whereby sGC activation is mediated by both direct interaction between the H-NOX and catalytic domains as well as allosteric interactions through the intervening PAS and helical domains (28). The apparent crucial role of flexible linkers as well as their dynamic fluctuations observed for sGC are common themes among signaling proteins (29).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous Trp residues located in βHNOX (Trp22), βGC cat (Trp602), αPAS (Trp352), αCC (Trp466), and αGC cat (Trp669) were used as FRET donors, and MANT-dGTP bound to the catalytic domain was used as a FRET acceptor [99]. While the low quantum yield of Trp residues make them suboptimal FRET partners [100], changes in FRET efficiency were observed in this study.…”
Section: Protein-protein Interactions Regulating Gc-1 Activitymentioning
confidence: 95%